OP0299 Susceptibility To Ankylosing Spondylitis Is Influenced Independently by Two Closely Adjacent Runx3 Snps, That Show Strong Functional Effect in Different Cell Types. (15th July 2016) - Vecellio, M.L.; Roberts, A.R.; Wordsworth, B.P.
Abstract : Background: More than 60 genes are associated with ankylosing spondylitis (AS), many of which ( RUNX3, EOMES, TBX21, ZMIZ1, IL23R, IL6R, ERAP-1, IL7 and IL7R) are involved in diverse immunological processes. 1 To understand the functional basis for these genetic associations is one of the greatest scientific challenges in complex polygenic diseases. For example, the association between AS and the single nucleotide polymorphism (SNP) rs4648889 located in a 2kb regulatory locus upstream the promoter of RUNX3 can be explained by allele-specific effects on transcription factor (TF) recruitment (including IRF4) that alter gene expression, specifically in CD8+ T-cells. 2 Objectives: 22 SNPs in the RUNX3 locus were initially found to be associated with AS. Here we focus on an independently associated SNP adjacent to rs4648889 which affects gene regulation in CD14+ monocytes. Methods: We used the Encyclopedia of DNA Elements (ENCODE) data to dissect the epigenetic and transcriptional landscape of the RUNX3 locus; we performed in silico analysis and in vitro functional studies to characterize the effects of this particular genetic variant, providing critical functional evidence for its role in AS. Results: (1) Conditional analysis on 4230 AS cases and 9700 matched controls established the primacy of rs4648889 association (1.3×10 –14 ) with AS in this region. However, there was also an independent second signal (1.7×10 –7 ) with rs4265380, adjacent to rs4648889, highlighting the importance of this locus and a likely functional role for rs4265380 . (2) ENCODE data on CD14+ monocytes, revealed a robust peak for DNA accessibility (DNase1 Hypersensitivity) and TFs ChIP-seq overlapping rs4265380 . There was also a strong overlying peak for histone modification H3K4Me1, normally associated with active regulatory region. (3) The effect of the rs4265380 dimorphism on TF binding was evaluated by electrophoretic mobility shift assays (EMSA) using nuclear extract from U937 and THP-1 (monocyte-derived cell lines) focusing on specific TFs involved in monocyte regulation, inflammation and chromatin modifiers (C-Fos, p300 i.e.). (4) Analysis of the expression of inflammasome-related genes revealed some striking differences (i.e CARD6 and IL-6, upregulated of 5 and 177 fold, respectively) influenced by the rs4265380 genotype. Conclusions: We have identified functional differences in the transcriptional regulation of RUNX3 associated with AS-associated SNPs at this locus. Two individual adjacent SNPs exert their independent effects in two separate cell types (CD8+ T-cells and monocytes). These observations are critically important not only in identifying cell types that play a pathogenic role in AS but also in defining potential therapeutic drug targets. References: IGAS et al. Nat Genet. 2013 Jul;45(7):730–8 Vecellio M. et al, Ann Rheum Dis. 2015 Oct 9 pii: annrheumdis-2015–207490 Disclosure of Interest: None declared